An Exploratory Review of Oil Price and Economic Growth in Five Oil-Importing Middle-Income Countries in SSA: Array - Akinsola, Motunrayo; Odhiambo, Nicholas (The Journal of Accounting and Management, 2020)
This paper is an exploratory review of the dynamics of oil price and economic growth in five middle-income oil-importing countries in sub-Saharan Africa, namely: Botswana, Kenya, Mauritius, Namibia and South Africa. The energy sources, as well as the effect of oil price on economic growth, are highlighted for each country. The study finds that energy sources in middle-income countries are not uniform. While Botswana has an almost equal share of oil and coal as its major energy sources, South Africa main energy source is coal and Namibia and Mauritius depends mostly on oil for their energy needs. Kenya depends highly on biofuel for its energy needs. However, South Africa is the largest oil importer because it also serves as oil exporter to most of its Southern African neighbouring countries. The effect of oil price, therefore, varies depending on the level of oil in the energy mix of individual countries.